Identifikasi Masalah Dalam Penyusunan Apbdes Tahun 2024 Di Desa Tandaigi Kecematan Siniu Kabupaten Parigi Moutong - Lanande, Idrus S.; Mufti, Muhammad Irfan; Ferianto, Fiki (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The process of formulating the Village Budget (APBDes) by the Village Government and also the BPD of Tandaigi Village as a representative of the community has not carried out its control and representation functions optimally. In addition, the Village Apparatus' understanding of technical budgeting regulations is still limited and community participation is still low. This study aims to analyze the identification of problems and actors in the preparation of the 2024 Village Budget (APBDes) in Tandaigi Village, Siniu District, and also identify the actors involved and the problems that arise in the budget preparation process. This study uses the theory of Thissen and Warren E. Walker, which emphasizes the importance of understanding the substance of the problem, the actors involved, and the institutional characteristics in the budget preparation process. The method used is a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The results of the study indicate that the process of preparing the APBDes in Tandaigi Village contains various public problems that are not accommodated in the preparation of the APBDes. The involvement of actors is dominated by the Village Government, while other actors cannot influence the decisions that have been taken. The involvement of each institution has not been fully optimal due to several factors, such as the dominance of decision-making by certain parties and a lack of technical capacity and resources. This research provides insight into the importance of comprehensively identifying issues and actors to achieve village financial governance that is relevant to community needs.